Peran stres oksidatif dalam hipertensi esensial: Systematic review - Nur Ramadani Arban; Mohammad Zulkarnain; Emma Novita (Jurnal Kesehatan Andalas, 2026)
The role of oxidative stress in essential hypertension: A systematic review Oxidative stress plays a crucial role in the pathogenesis of essential hypertension. It leads to endothelial dysfunction, reduced nitric oxide (NO) bioavailability, and increased arterial stiffness, all of which contribute to elevated blood pressure. Objective: To analyze the role of oxidative stress in the pathogenesis of essential hypertension. Methods: This study was a literature review conducted by searching PubMed, ScienceDirect, and Cochrane databases from 2021 to 2025 using the keywords “Hypertension AND Oxidative Stress AND Correlation.” Of the 2700 identified articles, six studies met the inclusion and exclusion criteria and were analyzed further. Results: All selected studies demonstrated a strong relationship between oxidative stress and hypertension. Increased production of Reactive Oxygen Species (ROS) impairs endothelial function, reduces NO levels, and increases arterial stiffness. Interventions using antioxidants, such as melatonin, and dietary nitrates improved vascular function and oxidative balance. However, the outcomes varied depending on the type and dosage of antioxidants used. Conclusion: Oxidative stress plays a key role in the development of essential hypertension through endothelial damage, vascular dysfunction, and activation of the renin-angiotensin system. Antioxidant-based interventions, particularly melatonin, show promising potential to improve redox balance and reduce blood pressure. Further studies are needed to establish their long-term efficacy and safety. Keywords:  antioxidants, essential hypertension, oxidative stress, melatonin, nitric oxide